Computational analysis of differential interactions between cyclins and CDKs. - See, Pui Fun. (2010)
Members of cyclin-dependent kinase (CDKs) family in complex with their cognate regulatory subunits, cyclins, have been implicated in the control of essential cellular activities. Recent gene-targeted knockout studies performed on different cyclin-CDK complexes opposes the ‘classical model’ of cell-cycle regulation. Moreover, structural studies have yet to demonstrate precisely the molecular mechanisms behind the selectivity of cyclins for a preferred subset of CDKs; with incomplete structural details concerning their interactions. To understand if selectivity does exist at the interface between multiple cyclin-CDKs complexes, the present work describes the molecular models for binary complexes of yet-to-be crystallized cyclin-CDK assemblies. Classically, cyclinA2 and cyclinE1 is found to complex with CDK2 while two D-type cyclins are found to complex with CDK4. With the aid of a priori interface predictions, data-driven docking study using HADDOCK was performed. Four structural models of cyclinA2-CDK4, cyclinE1-CDK4, cyclinD3-CDK2 and cyclinD1-CDK2 complexes were generated. Assessment of the models showed that cross-interactions may occur between cyclins and CDKs. Though the quality of binding could be attributed to the presence of specific subsets of inter-molecular contacts, a conserved core set of interactions were found at the interfaces. This suggests that the consensus view of selectivity of cyclins for a preferred subset of CDKs needs to be re-examined.